The future of political science 100 perspectives - King, Gary 1958- (Routledge, 2009)
This book contains some of the newest, most exciting ideas now percolating within political science. One hundred authors each contribute a brief essay about a single novel or insufficiently appreciated idea on some aspect of political science.